Formulasi dan Evaluasi Sediaan Sheet Mask dari Ekstrak Etanol Kulit Buah Pir (Pyrus Bretschneideri) Sebagai Antioksidan dengan Metode DPPH - Monica Suryani; Manahan Situmorang; Steven Tandiono; Supartiningsih Supartiningsih (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Pear skin contains flavonoids which have potential as antioxidants. Considering the existence of humans as social creatures, interacting with each other requires self-confidence to be well accepted. For this reason, humans need self-care to appear charming, attractive and full of self-confidence. Masks are a type of cosmetic treatment that is well known and widely used. The mask works deeply to remove dead horn cells on the skin. This research aimed to determine the potential antioxidant activity of the ethanol extract of pear peel (Pyrus bretschneideri) which was formulated as a sheet mask preparation. Extraction was carried out by maceration using 96% ethanol to obtain pear peel extract. The antioxidant activity test method was carried out using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The results obtained from the concentration of the sheet mask preparation of pear peel extract (Phyrus bretschneideri) were homogeneous and stable. The pH results obtained from F0 (5,1), F1 (5,4), F2 (5,5), F3 (5,6), are still within the safe range of facial skin pH. The results of the antioxidant activity test showed that the IC50 value for F1 was 84.58 ppm with intensity (Strong), F2 69.96 ppm with intensity (Strong), and F3 63.79 ppm with intensity (Strong).